Analysis of Messages and Perceptions of Liberal Feminism in Disney's Aladdin Movie - Br. Silalahi, Elfrida; Risa Febrianti (English Lecturers and Teachers Association (ELTA), 2024)
This study aimed to analyse the Characters of Jasmine on Aladdin, represents liberal feminism. One Disney heroine who epitomizes the strength and bravery of a woman is. This study looks for feminist view points in Princess Jasmine's character via the lens of liberal feminism discuss in methods of qualitatvies descriptives. It will also look at how the audience's perceptions of gender roles and social equality are influenced by the character. The study's findings should deepen our understanding of how female characters are portrayed in the entertainment business and how role models like Jasmine affect young women's generation expectations and perceptions of gender roles in real society especially in Indonesia and also provide insight into the potential of animated films to present more inclusive and progressive messages of feminism to audiences from diverse backgrounds. Key words : Liberal Feinism, Character , Disney’s Aladin Movie